Drug free REmission/low disease activity after cessation of tocilizumab (Actemra) Monotherapy (DREAM) study. Issue 1 (January 2014) - Nishimoto, Norihiro; Amano, Koichi; Hirabayashi, Yasuhiko; Horiuchi, Takahiko; Ishii, Tomonori; Iwahashi, Mitsuhiro; Iwamoto, Masahiro; Kohsaka, Hitoshi; Kondo, Masakazu; Matsubara, Tsukasa; Mimura, Toshihide; Miyahara, Hisaaki; et al.
Abstract: Objectives To investigate the duration of remission and low disease activity (LDA) after cessation of tocilizumab (TCZ) treatment in rheumatoid arthritis patients who showed remission or LDA as assessed by DAS28 in response to preceding TCZ monotherapy, and to explore the factors contributing to prolonged efficacy duration. Methods Disease activity was monitored for 56 weeks. The rate of continued efficacy was estimated by Kaplan–Meier curves. Results A total of 187 patients were eligible. At baseline of this study, median disease duration was 7.8 years, preceding TCZ treatment period was 4.0 years and DAS28 was 1.5. The rate of continued LDA at 52 weeks was 13.4 % according to the Kaplan–Meier estimate. 19 patients (10 %) were completely drug-free and 17 patients (9.1 %) fulfilled DAS28 remission at 52 weeks. Multivariate Cox regression analysis identified low serum IL-6 and normalisation of MMP-3 levels at cessation of TCZ as independent predictive markers for longer duration of LDA. In patients with low serum IL-6 (<12.9 pg/mL) and normal MMP-3 levels, the rate of continued LDA reached 38.0 % at 52 weeks. Conclusions TCZ monotherapy may induce biologics-free remission or LDA without concomitant use of synthetic DMARDs. Serum levels of IL-6 and MMP-3 are useful markers for identifying patients who could discontinue TCZ without acute disease flare.